Pelatihan Peningkatan Menulis Teks Berita Melalui Pendekatan Genre-Based bagi Siswa SMA Negeri 1 Stabat - Humaizi Humaizi; R. Hamdani Harahap; Muhammad Yusuf (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2024)
In order to produce news that is interesting to read and easy for readers to understand, skills are needed, one of which is writing skills. With writing skills, someone can express events into news that needs to be written into a news article that is ready to be published in the mass media. The partners involved in this service program are students at SMA Negeri 1 Stabat where the main problem experienced by the partners is the students' lack of understanding in writing news texts. The location for this activity is at SMA Negeri 1 Stabat, Langkat, North Sumatra. This program consists of preparation, implementation, monitoring and evaluation stages. Training activities regarding this were carried out on 23 and 30 September 2023 offline and online using lecture, direct training, discussion and question and answer methods. The conclusion that can be drawn is that participants in service activities write news texts that must fulfill several rules that are in accordance with the genre-based approach, namely that there must be a news-worthy event, source, and answer the 5W=1H information. Furthermore, this activity is able to increase students' literacy in writing news as evidenced by the results of news written by students.